2019
DOI: 10.1111/jwas.12663
|View full text |Cite
|
Sign up to set email alerts
|

Dietary quercetin improved the growth, antioxidation, and flesh quality of grass carp (Ctenopharyngodon idella)

Abstract: To investigate the effects of dietary quercetin on growth, antioxidation, and flesh quality of grass carp, Ctenopharyngodon idella, six diets were prepared with quercetin inclusion rates of 0 (control diet), 0.1, 0.2, 0.4, 0.6, and 0.8 g/kg. Grass carp with a body weight of 13.3 ± 0.1 g were fed with one of the six diets for 60 days. The weight gain (WG) showed a quadratic relationship with dietary quercetin levels; the supplementation of 0.4 g/kg quercetin significantly improved WG (+4.73%) and decreased feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The supplementation of 0.2–1.6 g/kg quercetin in diets significantly increased weight gain and decreased FCR of tilapia (Zhai & Liu, 2013). The studies on olive flounder ( Paralichthys olivaceus ) (Shin et al., 2010), grass carp (Xu et al., 2019) and blunt snout bream ( Megalobrama amblycephala ) (Jia et al., 2019) also indicated that dietary quercetin improved the growth performance. In this study, the supplementation of 0.8 and 1.0 g/kg rutin also increased the weight gain and decreased FCR ( p < .05) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of 0.2–1.6 g/kg quercetin in diets significantly increased weight gain and decreased FCR of tilapia (Zhai & Liu, 2013). The studies on olive flounder ( Paralichthys olivaceus ) (Shin et al., 2010), grass carp (Xu et al., 2019) and blunt snout bream ( Megalobrama amblycephala ) (Jia et al., 2019) also indicated that dietary quercetin improved the growth performance. In this study, the supplementation of 0.8 and 1.0 g/kg rutin also increased the weight gain and decreased FCR ( p < .05) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that phenolic acids [34], avonoids [35], and polysaccharides [36] inhibited the colonization of pathogenic bacteria in the intestines, increased the number of bene cial bacteria and enhanced the intestinal nutrient absorption. In grass carp, the EU active compounds such as chlorogenic acid [22], quercetin [23] and baicalein [37] have been reported to signi cantly promote the growth performance. Therefore, the growth improvement by dietary ELE is the combined effect of various active compounds.…”
Section: Effects Of Eucommia Extracts On the Growth Performancementioning
confidence: 99%
“…Generally, barks contain more lignin and iridoids, while leaves contain more phenolic acids and avonoids [39]. Previous studies in our laboratory have shown that dietary phenolic acids (chlorogenic acids) [9] and avonoids (quercetin) [23] produced more positive effects on growth of grass carp than iridoids (geniposide and geniposidic acid) did [24][25].…”
Section: Effects Of Eucommia Extracts On the Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…This functional supplement is a flavonoid derived from milk thistle commonly used to treat liver failure and fetal diseases. Xu et al () pinpointed some positive effects of supplementing grass carp ( Ctenopharyngodon idella ) feeds with quercetin extracted from the traditional herbal medicine Eucommia ulmoides , which is also a flavonoid compound.…”
Section: Disease and Health Managementmentioning
confidence: 99%